2015
DOI: 10.1097/jom.0000000000000505
|View full text |Cite
|
Sign up to set email alerts
|

Pregnant Employee Protection Program in a Large Chemical Company

Abstract: Pregnancy complication rates in this chemical company are not statistically elevated than that in the general population, as suggested in a previous study. The protection program may play a role in preventing complications that may have occurred.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
(17 reference statements)
0
2
0
2
Order By: Relevance
“…Even if MPL represents a collective right, health protection for pregnant employees is applied individually and each employee benefits from different resources (De Koninck and Malenfant 2001). Finally, the study by Frey et al (2015), carried out in a chemical company in Germany, showed that the company's commitment to a healthy working environment was a significant element of support to MPL: "[…] an in-depth counseling during regular annual safety instructions enhances the awareness of women of possible chemical risks during pregnancy" (Frey et al 2015, p. 970).…”
Section: Physical and Social Environmentmentioning
confidence: 99%
“…Even if MPL represents a collective right, health protection for pregnant employees is applied individually and each employee benefits from different resources (De Koninck and Malenfant 2001). Finally, the study by Frey et al (2015), carried out in a chemical company in Germany, showed that the company's commitment to a healthy working environment was a significant element of support to MPL: "[…] an in-depth counseling during regular annual safety instructions enhances the awareness of women of possible chemical risks during pregnancy" (Frey et al 2015, p. 970).…”
Section: Physical and Social Environmentmentioning
confidence: 99%
“…Through the establishment of a team mechanism and the application of various effective methods, in order to play the complementary role and synergy between individual human resources, the overall work of the personnel team Efficiency, effect, ability, and energy greatly exceed the combination of individual ability and efficiency. The fourth is to pay attention to grasping the principle of periodic dynamics [24][25]. This principle is that when a group is configured, it enters the group life cycle including formation, growth, development, aging, and extinction [26].…”
Section: ) Reasonable Allocation Of Human Resourcesmentioning
confidence: 99%
“…Gleichzeitig ist dem Schutz von Mutter und Kind Rechnung zu tragen. Im Rahmen der verpflichtenden Gefährdungsbeurteilung des Arbeitsplatzes (§§ 10 11 12 13 MuSchG) sollen sogenannte „unverantwortbare Gefährdungen“ (§ 9 MuSchG) identifiziert und durch Umgestaltung der Arbeitsbedingungen, Versetzung oder durch ein Beschäftigungsverbot als „ultima ratio“ ( 11 , § 13 MuSchG) ausgeschlossen werden. In den operativen Fachgebieten sollte hier der Fokus nicht nur auf den Tätigkeiten im Operationssaal liegen.…”
Section: Introductionunclassified
“…Die tatsächlichen Arbeitsbedingungen während der Schwangerschaft sind in Deutschland wenig untersucht [12,13]. Ziel der vorliegenden Arbeit ist es, die vorherrschenden Arbeitsbedingungen aus Sicht der schwangeren Ärztinnen operativer Fachgebiete im Rahmen einer Befragung zu erheben.…”
Section: Introductionunclassified